Building Effective, Accountable, and Inclusive Institutions in Europe and Central Asia : Lessons from the Region - Arizti, Pedro; Boyce, Daniel J.; Manuilova, Natalia; Sabatino, Carlos; Senderowitsch, Roby; Vila, Ermal (World Bank, Washington, DC, 2020)
Countries around the world are facing the need to build effective, accountable, and inclusive institutions. There has never been a more important moment to tackle this agenda, as countries grapple with increasing fragility and migration flows, more complex service delivery requirements, and greater demands for transparency and inclusion, all in a more resource-constrained environment. Moreover, the COVID-19 (Coronavirus) pandemic crisis has provided new evidence of the need for effective, accountable, and inclusive government responses. Governments’ capacity to respond to these complex challenges is understandably stretched, but this has not limited the rise of citizens’ expectations. Instead, it has often increased tensions and, in some cases, has affected the trust between governments and their citizens. This publication builds on the World Bank’s vast engagement across ECA and on the 2019 regional governance conference. It consists of six chapters, each corresponding to one of the governance areas around which governments across the world organize their institutional functions. Each chapter contains background and analysis by World Bank specialists, complemented by country case studies authored by regional experts and policymakers.